Developing ESP students' online text reading performance and strategies in small group discussion - Erlangga, Fajar; Setiawan, Slamet; Anam, Syafi'ul (LITERA, 2024)
Reading English text is often regarded as a difficult task by English for Specific Purposes (ESP) students during their individual reading time. Therefore, this research investigates the impact of a small group discussion on ESP students' online text reading performance and strategies. The quantitative research, employing a pre-experimental design, purposively recruited 90 students from the Computer Science and Engineering Faculty. The data were collected through pre- and post-assessments on reading comprehension and a survey on reading strategies. Analyzed using SPSS 27.0, the data of the research show that the small group discussion highly affects reading performance of ESP students. Besides, their reported reading strategy use demonstrates a high frequency of use in all three strategy categories (PROB, GLOB, SUP), with no significant difference found in all categories by age and major. In conclusion, the implementation of a small group discussion in the ESP classroom can effectively improve the online text reading performance and develop reading strategies of the students. It also positively implies that educators can employ a small group discussion to promote other reading aspects in various educational settings.